The Meaning of Understanding and the Open Body Some implications for qualitative research (Existential Analysis: Journal of the Society for Existential Analysis, 2004)
This paper wishes to address the nature of embodied understanding and how such considerations may clarify the purpose and path of phenomenologically-oriented qualitative research.